Children who resist postseparation parental contact a differential approach for legal and mental health professionals - Fidler, Barbara Jo, 1956-; Bala, Nicholas C.; Saini, Michael (New York ; Oxford : Oxford University Press, 2012)
This title is a critical, empirically based review of parental alienation that integrates the best research evidence with clinical insight from interviews with leading scholars and practitioners.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Children of divorced parents -- Psychology; Children of separated parents -- Psychology; Separation anxiety in children; Divorced people -- Counseling of; Alienation (Social psychology)